Propuesta modelo de gestión para la producción de la empresa Condimar S.A - Valderrama Jiménez, Diana Cateryne; Fonseca Barrios, Nubia Esther (Universidad Antonio Nariño, 2023)
This research paper aims to evaluate the current production system of Condimar S.A. company based on a mixed-method research model to achieve a better comprehension of the problem proposed in the study; thus, workshops are executed with the software developing personnel, and news formats are implemented, allowing better production control. Meanwhile, the outcomes will show a decrease in the reprocessing incidents presented inside the company.